Ecotourism of Tropical Regions with Renewable Energy Perspective in Indonesia - Daniarta, Sindu; Farasi, Yose Ardhani (KnE Energy, 2015)
Indonesia is archipelago country with natural resources and population 230 million in 2010. The natural resources areas are mining, forestry, natural tourism. Indonesia has much natural tourism without electricity. At this time, the issues about electricity are growing rapidly. Renewable energy system is most contribution to generate electricity. Photovoltaic and wind turbine are usually for renewable energy system in tropical region. HOMER Energy software system is used to simulate the model of ecotourism with renewable energy system. In future can be used as a reference in the development of renewable energy based Ecotourism Island in Indonesia Keywords : Ecotourism; HOMER Energy; renewable energy; wind turbine